Fluxo e acesso assistencial: mecanismos da regulação em saúde entre a atenção básica e a especializada - Tangerino, Lariana Cássia Pereira (Universidade Federal de São Carlos, 2018)
The health like right in Brazil, guided by equal terms have been affected by the current situation of the country due to its diversity and magnitude of both territorial and regional features. The Single Health System and some its policies (Basic Attention National Policy, Health Attention Systems, National Regulation Policy) seek for guaranteeing care integrality, promoting accessibility with continuous assistance and rational operation of the existing resources. The aim of this study was to analyze the performance of a municipal regulation system within the scope of the relations among Basic Attention, Specialist Assistence and Regulation Center, in order to provide a reflection about both the potential and the improvement opportunities in the services of scheduling medical appointments and exams. The conduct of this research was based on the qualitative approach assumption. The chosen city for the research development was Araraquara (SP). For data collection method, there were meetings to hold focus groups. The participants were the administrative agents, nurses and doctors of Basic Attention from a predetermined area, people responsible for scheduling appointments and the servants of Regulation Center, a total of 31 people. Data was examined from the point of view of the subject content analysis. The 31 participants were: 5 nurses, 14 doctors, 11 administrative agents and 1 licensed practical nurse. After the exhausting reading of the recorded and transcribed answers, it was possible to group them according to the contexts they referred to, in main topics and their categories. The main catalogued issues were: “The Health Care Attention System”, “The City Scheduling System”, “The use of protocols for Clinical Evaluation” and “The Permanent Education in health”. Through this data, it was possible to identify that the already established actions to review the scheduling system in such city have provided significant improvements in the employments’ work routine and also facilitated patients’ access to health. However, these mechanisms, have also brought some challenges that require confrontation by management and workers in order to solve communication problems, information systems, document records, employee improvement and qualification of their professionals.It is suggested to the municipality to face these challenges, adjustments in the use of protocols for clinical evaluation, provide systematized training for all categories of Basic Attention, have matrix support and use of only one information system.
Flow ans assistance acess: mechanisms regulation between basic and specialized health care
Keywords: Gestão em saúde; Regulação em saúde; Assistência integral à saúde; Sistemas de saúde; Políticas públicas de saúde; Modelos de atenção; Health management; Health regulation; Integral health assistence; Health care systems; Public health policies; Attention models; CIENCIAS DA SAUDE::SAUDE COLETIVA; CIENCIAS DA SAUDE::SAUDE COLETIVA::SAUDE PUBLICA